Karakteristik Distribusi Maxwell-Boltzmann - Artina Puspita; Dewi Murni (Journal of Mathematics UNP, 2018)
Abstract – This study discusses the characteristics of Maxwell-Boltzmann distribution. Each distribution has its own characteristics. The characteristics can be seen in the parameters are mean, variance, skewness, kurtosis, moment generating function and characteristic function. The purpose of this study is to determine the characteristics of the Maxwell-Boltzmann distribution. The steps of this research are looking for the mean, variance, skewness, kurtosis, moment generating function, and characteristic function of the Maxwell-Boltzmann distribution. The results of this research were obtained the parameters of the Maxwell-Boltzmann distribution: mean variance, skewness, kurtosis, generating function of the momen and characteristic function.